STRATEGI PENGEMBANGAN USAHA OLAHAN KEDELAI (Studi Kasus di CV. Intan Alami, Kabupeten Garut) - Andika, Alif; Yudha, Eka Purna (Universitas Galuh, 2023)
ABSTRACTThis study aims to determine alternative strategies in developing soybean processing businesses in CV. Intan Alami Garut Regency through SWOT analysis and QSPM analysis. The method used in this study is a qualitative method using primary data through observation and interviews and secondary data in the form of scientific journals and literature studies. Based on the research results it can be concluded that the strength of CV. Intan Alami in developing her business is access to information and market opportunities with a weakness in determining the selling price. The main opportunity for CV. Intan Alami in developing its business is the use of technology owned by the company with the main weakness being the effectiveness of marketing, advertising and promotion. Based on the SWOT analysis and IE analysis, the main strategies that need to be carried out are market penetration strategies and product development strategies.